Pengaruh Brand Equity terhadap Keputusan Pembelian Semen Bosowa (Studi Kasus pada Konsumen di Kelurahan Antang Makassar) - Hanafi, Muh. Alam Nasyrah (P3M STIEM, 2016)
Brand Equity against Influence Purchasing Decisions of cement (Case Study Consumer Village Antang In Makassar). This study aims to (1) analyze the effect of brand equity consists of brand awareness, perceived quality and brand loyalty on purchase decisions of cement in the Village Antang Makassar. (2) Analyze the most dominant variable influence on purchasing decisions of consumer in the Village Antang Makassar. This study uses quantitative analysis is multiple regression analysis. The population in this study are consumer RW III Antang Manggala Makassar from the year 2009 - 2011 as many as 200 people